Analisis Implementasi Kebijakan Pengenaan Kompensasi Terhadap Pelampauan Nilai Koefisien Lantai Bangun di Lingkungan Pemerintah Provinsi DKI Jakarta - Ady Saputro; Achmad Lutfi (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2021)
This study dicusses the space on   the coefficient of the building floor, especially buildings in the DKI Jakarta area in the study of the application of the policy of imposing compensation for exceeding the building floor coefficient value and the factors that influence the implementation of policies within the DKI Jakarta Provincial Government. The purpose of this study is to analyze the implementation of the policy regarding the imposition of compensation for exceeding the building floor coefficient value and find factors that hinder the implementation of the policy implementation. This study uses the theory of Street Level Beauracrats from Michael Lipsky and the theory of influencing factors from Grindle. This research was conducted through an approach through interviews and study literature. This one of the study indicate that the implementation of the policy has been going well, and the community is enthusiastic in responding to every policy issued by the DKI Jakarta Provincial Government. Then a factors that influence the implementation of the policy are the strategic actors involved in formulating policies